Study of open versus closed reduction of mandibular condyle fractures - Gareikpatii, Nagaraj (International Surgery Journal, 2021)
Background: Condylar fractures of the mandible are a commonest occurrence in maxillofacial surgery. Many surgeons prefer closed therapy with maxillomandibular fixation, while open treatment with rigid internal fixation has become more common in recent years. This study provides a comparative evaluation of open and closed reduction of the mandibular condyle. Methods: The 50 patients with condylar fractures were treated with open and closed reduction as per the requirement. Results: A higher incidence of unilateral segmented condylar fractures were seen in young adult males. Open reduction and internal fixation (ORIF) with a combined approach was the preferred treatment of choice with fewer post-op complications. Conclusions: ORIF is a suitable technique in the treatment of condylar fractures as it promises few complications.